PERBANDINGAN ANALISIS KEUANGAN LEMBAGA KEUANGAN NON BANK PT. TRUST FINANCE INDONESIA TBK. DAN PT. BUSSAN AUTO FINANCE - Dg Macenning, A. Reski Almaida; Burhamzah, Rahmat (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to compare the financial performance of two non-bank financial institutions, namely PT Trust Finance Indonesia Tbk and PT Bussan Auto Finance, in the year 2023 by using financial ratio analysis, including liquidity, solvency, profitability, and operational efficiency (BOPO) ratios. The background of this research is based on the importance of evaluating financial performance to assess managerial effectiveness and the competitiveness of financing companies amid economic dynamics. The method used is descriptive quantitative with a comparative approach. The data analyzed consists of the annual financial reports of both companies published in 2023. The results indicate significant differences in financial structure and operational efficiency between the two companies. PT Bussan Auto Finance tends to demonstrate better operational efficiency, as reflected in a lower BOPO ratio, while PT Trust Finance shows more fluctuating profitability ratios. This study provides practical implications for investors, company management, and regulators in considering financial efficiency and stability when making strategic decisions.